Republic of Moldova : Technical Assistance Report-Public Sector Debt Statistics. (IMF Staff Country Reports; Country Report, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission to improve public sector debt statistics (PSDS) in Moldova. The IMF mission found that Moldova continues to improve their recording, compilation and dissemination of PSDS reflecting potential fiscal risks, but faces some statistical challenges going forward. The adoption of recommendations, along with comprehensive monitoring of on-lending and contingent liabilities, would increase the Moldovan policymaker's ability to forecast future fiscal risk and actively monitor the gross debt of all public-sector institutions in line with the new Fiscal Risk Statement. This would translate into a sound Public Finance Management structure and allow for more accurate macroeconomic surveillance and analysis.